ChemInform Abstract: Synthesis and Spectral Characteristics of Novel Fluorescent Dyes Based on Pyrimido[4, 5‐d][1, 2, 4]triazolo[4, 3‐a]pyrimidine. Issue 36 (September 2015) - Mohadeszadeh, Manijeh; Rahimizadeh, Mohammad; Eshghi, Hossein; Shiri, Ali; Gholizadeh, Mostafa; Shams, Alireza
Abstract Six title compounds of type (VI) are prepared and their UV/VIS and fluorescence spectra are measured.